Catfish - Advances, Technology, Experiments 2022
DOI: 10.5772/intechopen.106380
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Challenges of Catfish Farming in the Small-Scale Industry in Southern Africa

Abstract: This chapter summarizes the successes and challenges of catfish farming in the small-scale industry in Southern Africa. Given that capture fisheries have been declining steadily over the years in many countries, aquaculture is generally expected to grow to meet demand. However, catfish production in most Southern African countries is low. This is despite the region having the most suitable temperature for the culture of freshwater fish species. In Southern Africa, catfish farming is one of the most important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Results showed that farmers' knowledge of using artificial feed for catfish culture was significantly improved by their formal education, indicating that if formal education changes by 1 unit (one number), then knowledge of using artificial feed for catfish production changes by 0.348 units. In order to maintain a catfish farm, such as feed management, education is considered to be essential (Esau et al, 2022) [19] . Both Sumon (2014) [47] and Yeasmin (2013) [53] found similar results.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%
“…Results showed that farmers' knowledge of using artificial feed for catfish culture was significantly improved by their formal education, indicating that if formal education changes by 1 unit (one number), then knowledge of using artificial feed for catfish production changes by 0.348 units. In order to maintain a catfish farm, such as feed management, education is considered to be essential (Esau et al, 2022) [19] . Both Sumon (2014) [47] and Yeasmin (2013) [53] found similar results.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%